Effects of Ecballium elaterium on brain in a rat model of sepsis-associated encephalopathy. Issue 1 (1st January 2017) - Arslan, Demet; Ekinci, Aysun; Arici, Akgul; Bozdemir, Eda; Akil, Esref; Ozdemir, Hasan Huseyin
ABSTRACT: Despite recent advances in antibiotic therapy, sepsis remains a major clinical challenge in intensive care units. Here we examined the anti-inflammatory and antioxidant effects of Ecballium elaterium (EE) on brain, and explored its therapeutic potential in an animal model of sepsis-associated encephalopathy (SAE) [induced by cecal ligation and puncture (CLP)]. Thirty rats were divided into three groups of 10 each: control, sepsis, and treatment. Rats were subjected to CLP except for the control group, which underwent laparatomy only. The treatment group received 2.5 mg/kg EE while the sepsis group was administered by saline. Twenty-four hours after laparotomy, animals were sacrificied and the brains were removed. Brain homogenates were prepared to assess interleukin 1beta (IL-1β), interleukin 6 (IL-6), tumor necrosis factor alpha (TNF-α), total antioxidant capacity (TAC), and total oxidant status (TOS). Brain tissue sections were stained by hematoxylin and eosin (H&E) to semi-quantitatively examine the histopathologic changes such as neuron degeneration, pericellular/perivascular edema and inflammatory cell infiltration in the cerebral cortex. We found a statistically significant reduction in brain tissue homogenate levels of TNF-α 59.5 ± 8.4/50.2 ± 6.2 ( p  = 0.007) and TOS 99.3 ± 16.9/82.3 ± 7.8 ( p  = 0.01) in rats treated with EE; although interleukin 6 levels were increased in the treatment group compared to the sepsis group, this was not statistically significant. Neuronal damage ( p  = 0.00), pericellular/perivascular edema and inflammatory cell infiltration ( p  = 0.001) were also significantly lower in the treatment group compared to those in the sepsis group. These data suggest that Ecballium elaterium contains some components that exert protective effects against SAE in part by attenuating accumulation of proinflammatory cytokines, which may be important contributors to its anti-inflammatory effects during sepsis.